Parâmetros bioquímicos em guppy (Poecilia vivipara) e jundiá (Rhamdia quelen) expostos ao zinco - Leitemperger, Jossiele Wesz (2019)
Anthropogenic activities such as agriculture, urbanization and mining may increase the contamination of the aquatic environment by metals. Zinc (Zn) is an essential mineral that is involved in many biological processes. However, this metal may have toxic effects on aquatic organisms. Therefore, the first objective of this work was to evaluate the bioaccumulation and the possible effects on biochemical parameters in silver catfish (Rhamdia quelen) exposed to 0.0; 0.1; 0.25 and 0.5 mg L-1 Zn for 96 h. As a second objective, was evaluated the behavioural and biochemical effects of guppy (Poecilia vivipara) exposed to Zn (500 μg L-1) in water with different salinity (25 ppt) or hardness (120 mg L-1 CaCO3). In the first experiment, the parameters analyzed in silver catfish were bioaccumulation, determination of thiobarbituric acid reactive substances measured through the malondialdehyde levels (MDA), protein carbonyl (PC), superoxide dismutase (SOD), catalase (CAT), glutathione S-transferase (GST), non-protein thiols (NPSH), ascorbic acid (AA) in the brain, gill, liver and muscle. The levels of glycogen, protein, lactate, ammonia, and amino acids were measured in liver and muscle. Zn accumulation was observed in gill (0.5 mg L-1), intestine and liver (0.25 and 0.5 mg L-1). MDA levels increased in the brain and decreased in liver and muscle at all concentrations tested. There was a decrease in PC in brain and increase in liver. CAT activity in liver was reduced in all exposed groups and GST activity decreased in brain (0.5 mg L-1) and in liver (0.1, 0.25 and 0.5 mg L-1). NPSH levels increased in muscle (0.5 mg L-1) and in gill (0.25 and 0.5 mg L-1) and AA in brain (0.5 mg L-1) and gill in all concentrations tested. Exposure to Zn also altered metabolic parameters, causing decreased levels of lactate and ammonia in the muscle, and decreased hepatic glycogen. There was increased levels of ammonia, amino acids and protein in the liver, and increased glycogen and amino acids in muscle tissue. In the second experiment, guppies were divided into 6 groups: control, Zn (500 μg L-1), salinity (25 ppt), hardness (120 mg L-1 CaCO3), salinity (25 ppt) + Zn (500 μg L-1) and hardness (120 mg L-1 CaCO3) + Zn (500 μg L-1). There was a decrease in the distance traveled by fish in hard water and the number of entries into the top region in hardness and hardness + Zn. Exposure to Zn recorded an increase in the maximum speed of the fish. Biochemical analyzes were evaluated in the whole body of the guppy, where MDA increased, except in the association between salinity and Zn. PC was not altered in the salinity group, in the other groups, there was an increased. Zinc group increased the total peroxides, the reactive oxygen species, the antioxidant capacity against peroxyl radicals, SOD and NPSH. And decreased the activities of acetylcholinesterase and Na+/K+-ATPase. The integrated biomarker response index (IBR) was calculated for each parameter to aid in the interpretation of the results and indicated that the hard water containing Zn had the greatest effect on the biochemical parameters of the guppies. With these results, we can conclude that Zn, even in relevant environmental concentrations, altered the biochemical parameters analyzed. There was metal accumulation in some tissues of silver catfish and alterations in its biochemical and metabolic parameters. Zinc also altered the parameters analyzed in the guppy, where neither the salinity nor the hardness was able to protect the fish from the damages caused by the metal.